Distinctive in vitro signal transduction profile of NLX‐112, a potent and efficacious serotonin 5‐HT1A receptor agonist. (14th June 2017) - Newman‐Tancredi, Adrian; Martel, Jean‐Claude; Cosi, Cristina; Heusler, Peter; Lestienne, Fabrice; Varney, Mark A.; Cussac, Didier
Abstract: Objectives: NLX‐112 (befiradol, F13640) is a selective serotonin 5‐HT1A receptor agonist. Although it has been tested in vivo, little has been reported on its in vitro signal transduction profile. Methods: NLX‐112 was tested on G‐protein activation, inhibition of adenylyl cyclase, ERK1/2 phosphorylation (pERK) and receptor internalization in recombinant cell lines. NLX‐112 was also tested on G‐protein activation in rat hippocampal membranes. Gα subunit mRNA expression in cell lines and rat brain tissue was quantified by quantitative PCR. Key findings: For all signalling measures, NLX‐112 exhibited agonist efficacy greater than for reference compounds ((±)8‐OH‐DPAT or buspirone), but similar to the endogenous agonist, serotonin, and was more potent for pERK than other responses. In rat hippocampal membranes, NLX‐112 stimulated 'total G‐proteins' but, unlike (±)8‐OH‐DPAT and buspirone, was more potent for Gαo activation. Cell lines predominantly expressed Gαi1 and Gαi2 mRNA, with low levels of Gαo, whereas in rat brain Gαo subunits showed highest mRNA expression. Conclusions: Unlike reference compounds, NLX‐112 was a highly efficacious agonist in vitro, preferentially activating pERK in cell lines and Gαo proteins in rat hippocampal membranes. However, Gα subunit mRNA levels differ markedly between rat brain and cell lines, warranting caution when extrapolating from recombinant systems to native tissues.